2021
DOI: 10.1007/s11126-021-09915-w
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress and Related Factors Among Hospital Nurses during the COVID-19 Outbreak in Korea

Abstract: COVID-19 is an ongoing worldwide infectious disease pandemic. The purpose of this study was to investigate post-traumatic stress and related factors among hospital nurses during the COVID-19 outbreak. The subjects of this study were 300 nurses who worked in three general hospitals that operated National Designated Isolation Unit (NDIU) wards during the COVID-19 outbreak. Self-reporting questionnaires were used to collect data on post-traumatic stress, general characteristics, and work-related information. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 22 publications
(22 reference statements)
3
19
1
3
Order By: Relevance
“…The survey of Wang Y. X. et al ( 2020) suggested that the incidence rate of PTSD among nurses was 16.83%. A Korean study stated that 36.7% of nurses were at risk of developing PTSD (Moon et al, 2021), which was significantly higher than our results. Most importantly, our study compared the prevalence of PTSD among nurses working within and outside Hubei during the early period of the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 92%
“…The survey of Wang Y. X. et al ( 2020) suggested that the incidence rate of PTSD among nurses was 16.83%. A Korean study stated that 36.7% of nurses were at risk of developing PTSD (Moon et al, 2021), which was significantly higher than our results. Most importantly, our study compared the prevalence of PTSD among nurses working within and outside Hubei during the early period of the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 92%
“…These articles published reports on the prevalence of doctors and nurses of different races (Asian, Caucasian). Fourteen studies could obtain doctors’ PTSD prevalence and sample size, 27 items the prevalence and sample size of nurses' PTSD could be obtained in the research; five studies[ 30 , 31 , 32 , 33 , 34 ] used offline self-filled questionnaires to conduct surveys, and the remaining 23 studies[ 14 , 10 , 11 , 12 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]were investigated online through the Internet. All studies were cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Long working hours, high work pressure, irregular diets gradually broke down the health of medical staff, which increased the risk of post-traumatic stress disorder. The study found that the work department was related to the risk of PTSD, and the medical staff working in the isolated departments were at higher risk of PTSD[ 30 , 39 , 42 ] In the isolation unit, the medical staff directly contacted the patient and worn protective clothing for a long time, and the risk of infection and psychological burden were relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that nurses and midwives were more likely to experience PTSD compared with healthcare professionals. 19 The 61.7% of nurses experiencing PTSD observed in this study, is higher than 22.8% in Korea, 27 35.21%, 28 in China and 57% in the United Kingdom. 19 The higher prevalence of PTSD in this study is understandable.…”
Section: Discussionmentioning
confidence: 54%